Hippocampal Abnormalities with Cortical Malformations in Epilepsy Patients - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The occurrence of various types and MRI appearance of hippocampal abnormalities in 220 patients with malformations of cortical development (MCD) were studied in various centers and large public hospital outpatient clinics in Germany and Austria.